A privatização do setor elétrico paulista: suicídio de um grupo. - Pedroso Neto, Antonio José (2005)
As from 1995, the companies of the electric sector in São Paulo underwent organizational changes that both preceded and made privatization viable. They were carried out by their own workers under the label modernization . The problem to be studied in this research was to understand how they unleashed the dynamics of change, since they were aware that the changes would lead to the dismantle of their own body. In the changing process, the guidelines they adopted depended on the external demands. However, under bourdieusian sociology perspective, we consider that they also depended on the measures adopted in each company, that is, they resulted from the interpretation and redefinitions of these demands by the agents interacting under the constraints of company s field of the power. The empirical research was centered in one of the companies: in its unions and professionals, fundamentally, in the modernization agents, which was led by a limited group of workers in higher ranks. The main sources of data were interviews, questionnaires, documents, and newspapers. In this research we verified that the cardinals from the higher clergy decided for the possibility of carrying out a downsizing conducted by themselves before they were exposed to a takeover in near future. We tried to present the constraints and the instigating perspectives that touched them, and also, how some of their actions concerted with some demands from union entities and professionals. We also verified that, in the presentation and justification of modernization, the cardinals from the higher clergy spread principles of reclassification and ranking of the company and of workers, as well as the idea of rescuing and transferring part of them to a new company . Modernizing would be the bridge. In this context of speech, they called upon the workers who would work on the modernization and selected those who would take part in a training program. In both of them, the offer of posts, beneath the demand, pointed to the establishment of a frontier between those who would be participants and those who would not, a symbolic line which separated those who had the ticket to join in the new company and those with an uncertain future. This border implied in the division and ranking of the whole of the workers, with consequences such as increasing differentiation, of individualization and internal competition crowned by a realignment with the cardinals from the higher clergy. Finally, it created social conditions of reception of speech and became a mechanism that allowed them to impose their prescriptions by means of symbolic violence. Yet, we verified that with modernization, the cardinals from the higher clergy had something to demonstrate to the possible buyers: a reengineering under study and implementation. With it, they had diagnoses and bases to give continuity to potential achievements: redesign of processes, gains in productivity and efficiency, redimensioning of staff, formalization of activities and know-how of the workers. In conclusion, the cardinals from the higher clergy initiated a changing process which involved the workers and acquired its own dynamic. Further to that, everybody realized that the studies and the implementations carried out had produced and would produce unpredictable and undesired consequences: The reengineering and the lack of definition as to the future, as a matter if fact, apply to all.